Perawatan Carryroller Belt Conveyor C101 pada mesin Incinerator dengan Metode Fishbone Diagram di PT Fajar Surya Wisesa,Tbk - Hidayat, Taufik; Saefulloh, Asep (JURNAL TEKNIK INDUSTRI, 2022)
Machinery is a very important sector in the production process in every company. Machine maintenance is a very important activity, so the interval of component replacement and machine maintenance must be scheduled more intelligently. incinerators as a tool to destroy waste and use the heat arising from the combustion of waste to be converted to steam production, where the steam is reused for the production process of making wrapping paper. And the Incinerator component is a conveyor belt used for the process of transferring the waste to be incinerated. The Ishikawa diagram or known as the fish bone diagram is one of the Seven Quality Tools methods used to find the cause of a problem. This method divides the problem into cause and effect which consists of several factors: machine, management, materials, manpower, environment, measurement, method. The result of this study is that there are factors that cause damage or stuck on the carry roller belt conveyor C101 there are 4 points including: a. Material (life time of material carrier rollers), b. Machine (excess load causing shaft damage), c. environment (environmental conditions and weather factors), d. Human (Lack of knowledge about conveyor belts).